Evaluation of cocoa varieties for shoot induction under in vitro condition - Sreelekshmi, S.; Suma, B.; Minimol, J.S.; Joseph, L. (Journal of Tropical Agriculture, 2020)
In vitro propagation in cocoa is a potential tool for the rapid multiplication of true to type plants. Single noded cuttings of 2-3 cm collected from the budded plants maintained in polyhouse were used as explants. The experiment was done in five varieties: CCRP 2, CCRP 6, CCRP 8, CCRP 15 and Scavina. The best surface sterilization of explants was achieved using Mancozeb 0.2 per cent for 30 minutes followed by Cefotxim 0.1% for 10 minutes and then ethyl alcohol 70 per cent for 3 minutes and mercuric chloride 0.1 per cent for 5 minutes. Axillary bud sprouting was induced in basal Woody Plant Media (WPM) fortified with 2- isopentinyl adenine (2ip) and Indole-3-Acetic Acid (IAA). The period of single shoot induction from leaf axils was lowest (8.41) in variety CCRP 15 in media WPM+2ip 1ppm+IAA 0.02ppm. Among the varieties, highest multiple shoot induction percentage (93.75%) was recorded in variety Scavina.